Pengaruh Penggunaan Media Pembelajaran Kahoot terhadap Hasil Belajar Siswa Melalui Pendekatan Game-Based Learning di SMP Negeri 21 Samarinda - Ayisa Rahmadani Fitria; Eko Subastian; Muhammad Rizki Adithia (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study aimed to determine the effect of using Kahoot learning media through a Game-Based Learning approach on students’ learning outcomes in Informatics subjects at SMP Negeri 21 Samarinda. This study employed a quantitative approach with a Quasi Experimental Design using a Non-Equivalent Control Group Design. The sample consisted of class VIII-B as the experimental group and class VIII-C as the control group. Data were collected through learning outcome tests (pretest and posttest) and student response questionnaires. The results showed that students’ learning outcomes in the experimental group improved higher than those in the control group. The average pretest score in the experimental group increased from 48.9 to 73.3 in the posttest with an average N-Gain score of 0.43, which was categorized as moderate, while in the control group the average pretest score increased from 61.9 to 76.3 in the posttest. The statistical test results showed a significance value of ≤ 0.05, indicating that H₀ was rejected and H₁ was accepted. Therefore, it can be concluded that the use of Kahoot learning media through a Game-Based Learning approach had a positive effect on students’ learning outcomes in Informatics subjects at SMP Negeri 21 Samarinda.